EL CONSUMO TRANSFRONTERIZO, SU PROBLEMA Y SITUACIÓN SOBRE SU TRATAMIENTO EN EL PERÚ - Freitas Vela, Freddy (Revista de Derecho, 2019)
The present investigation deals with the problem of cross-border consumers facingthe current and growing globalization of direct and virtual commerce. Likewise, itshows us which are the main difficulties that have arisen both in the previous stagesof the consumer relationship, and at the same moment in which the relationshipis formed as well as in the post-sale; given the potential distance between consumerand supplier, the different applicable laws and the competent authority to processa claim. Many of these problems have not yet been resolved, definitively, by the authoritiesof consumer protection in the world and there are many international organizationsthat recommend the adoption of various policies and standards thataim to mitigate, correct or seek solutions for these problems, all of which are still inthe extra process and auto composition level since the consumer protection authoritieshave failed to either establish effective collaboration mechanisms, or the conflictof the local jurisdiction is not overcome.In Peru, the rules of the Code for the Protection and Defense of the Consumer,applicable to cases of cross-border consumption with effects in our country, havebeen interpreted to the benefit of Peruvian consumers who perform these operations.However, its practical application is still quite complicated and economicallyburdensome, adding to the questionable effectiveness of the procedure against aforeign supplier. At the same time, INDECOPI, the consumer authority in Peru,continues to make efforts to try to provide consumers with innovative tools andtechnology that help solve their consumption problems. Some of these, such asthe next interactive platform to manage claims will also allow to solve problemsof a cross-border nature. Likewise, the agreement with its Chilean counterpart,SERNAC, is an important and innovative model that seeks to provide consumerswith an instrument in the face of potential problems that could arise in the massivecross-border consumption relationships that are made between citizens ofboth countries.
Keywords: Consumer protection; Cross border; INDECOPI; SERNAC